Characterizing the outcomes of metastatic papillary renal cell carcinoma. (16th April 2017) - Connor Wells, John; Donskov, Frede; Fraccon, Anna P.; Pasini, Felice; Bjarnason, Georg A.; Beuselinck, Benoit; Knox, Jennifer J.; Rha, Sun Young; Agarwal, Neeraj; Bowman, Isaac Alex; Lee, Jae‐Lyun; Pal, Sumanta K.; et al.
Abstract: Outcomes of metastatic papillary renal cell carcinoma (pRCC) patients are poorly characterized in the era of targeted therapy. A total of 5474 patients with metastatic renal cell carcinoma (mRCC) in the International mRCC Database Consortium (IMDC) were retrospectively analyzed. Outcomes were compared between clear cell (ccRCC; n = 5008) and papillary patients ( n = 466), and recorded type I and type II papillary patients ( n = 30 and n = 165, respectively). Overall survival (OS), progression‐free survival (PFS), and overall response rate (ORR) favored ccRCC over pRCC. OS was 8 months longer in ccRCC patients and the hazard ratio of death was 0.71 for ccRCC patients. No differences in PFS or ORR were detected between type I and II PRCC in this limited dataset. The median OS for type I pRCC was 20.0 months while the median OS for type II was 12.6 months ( P = 0.096). The IMDC prognostic model was able to stratify pRCC patients into favorable risk (OS = 34.1 months), intermediate risk (OS = 17.0 months), and poor‐risk groups (OS = 6.0 months). pRCC patient outcomes were inferior to ccRCC, even after controlling for IMDC prognostic factors. The IMDC prognostic model was able to effectively stratify pRCC patients. Abstract : We show that pRCC patients have significantly worse outcomes than ccRCC patients, that no targeted therapy to date is superior to one‐another, and that metastatic type I pRCC is far less common than type II but may convey a better survival outcome. Furthermore, this is the first study to demonstrate that the IMDC prognostic model effectively stratifies pRCC patients into good, intermediate, or poor‐risk groups, providing physicians with more evidence to inform patients of their expected prognosis.